Semantic validation of environmental observations data. (May 2016) - Shu, Yanfeng; Liu, Qing; Taylor, Kerry
Abstract: To facilitate data access, integration and analysis tasks, standardised markup languages are commonly used for communicating data from multiple sources. However, one issue with the use of standardised markup languages is that they generally fail to capture the constraints that are imposed on data contents. As such, semantic validation of data encoded in these languages becomes difficult. In this paper, we focus on one such language, the Water Data Transfer Format (WDTF), and present an approach for validation of WDTF data contents. We show that by using Semantic Web technologies, we can express those constraints not captured by WDTF and check their consistency with respect to data through a query reduction technique that allows existing reasoners to be used for data validation. Finally, we report on an experimental study of our approach and discuss some common errors that we found in data as exposed by the study. Highlights: We propose a semantic approach for validation of environmental data encoded in Water Data Transfer Format (WDTF). We provide a detailed description of the validation process, which includes constructing an ontology for WDTF, representing data and constraints in OWL/SWRL, and validating data with respect to constraints through a query reduction technique. We evaluate our approach by implementing a prototype and testing it on real WDTF data.